2010
DOI: 10.1002/cncy.20125
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐based FNAC of the thyroid

Abstract: BACKGROUND:The aims of this study were to analyze cytomorphological features of Tripath PREP (BD SurePath, Burlington, NC) preparations in thyroid nodules and to examine adequacy and accuracy of SurePath and frozen sections for both clinical outcome and histological diagnosis when applicable.METHODS:Gathered during a period of 4 years, 712 SurePath specimens of the thyroid were included. Histological (n = 207) or clinical follow‐up (n = 505) was available in all cases. During the same period, 253 frozen sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…We had analyzed and shown that the unsatisfactory or nondiagnostic rate, the sensitivity and specificity of LBC using LBCPREP2™ in the diagnosis of TC were 9.1%, 95.2%, and 100%, respectively (unpublished data). Previous reports have shown a diagnostic sensitivity of 76.3–96.1% and a specificity of 54.9–81% in thyroid nodule with TC for FNA with LBC using either ThinPrep™ or SurePath™ system 36, 37, 38, 39. The unsatisfactory or nondiagnostic rate of the LBC systems ranges from 8.2% to 22.5% in the literature 34, 37, 39.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We had analyzed and shown that the unsatisfactory or nondiagnostic rate, the sensitivity and specificity of LBC using LBCPREP2™ in the diagnosis of TC were 9.1%, 95.2%, and 100%, respectively (unpublished data). Previous reports have shown a diagnostic sensitivity of 76.3–96.1% and a specificity of 54.9–81% in thyroid nodule with TC for FNA with LBC using either ThinPrep™ or SurePath™ system 36, 37, 38, 39. The unsatisfactory or nondiagnostic rate of the LBC systems ranges from 8.2% to 22.5% in the literature 34, 37, 39.…”
Section: Discussionmentioning
confidence: 97%
“…In the ThinPrep™ system, cells are collected in a methanol‐based solution (Cytolyt™) and are then transferred on to a positively charged slide with a gentle positive pressure 23. In contrast, in the SurePath™, cells are collected in an ethanol‐based solution (CytoRich™), centrifuged, and are then slowly sedimented onto a poly‐ l ‐lysinated slide 36. These systems are useful for the occasional processing of a large amount of samples at large‐scale medical centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In series where the direct-to-vial method is used, and all of the cellular material is therefore submitted for cytologic analysis, the average cellularity is generally higher than with the split-sample method and the rates of inadequacy and false positivity decrease significantly [9,13,15,16]. Regarding the results of Geers and Bourgain [17] using the SurePath method, these authors did not achieve good results in terms of the inadequacy rate but there might be some reasons related to the technical differences between ThinPrep and SurePath (see Inadequate Smears). Nevertheless, they claimed a significant reduction of the false-negative diagnoses.…”
Section: Introductionmentioning
confidence: 96%
“…The LBC ThinPrep-processed slides may show a few ill-preserved cells at the periphery of the circle because transfer from the preservative solution to the specific slide requires positive pressure which may give rise to cellular artifacts. SurePath, according to Geers and Bourgain [17], yields an inadequacy rate of 25% in thyroid aspiration cytology. This result can probably be attributed to the low sedimentation rate of the colloid droplets which might hinder their inclusion in the final slide [17].…”
Section: Inadequate Smearsmentioning
confidence: 99%